IDENTIFICATION OF STUDENT ABILITY IN SOLVING MODEL OF NATIONAL ASSESSMENT IN KEFAMENANU EAST OF NUSA TENGGARA - Patrisius Nulle; Yohanis Ndapa Deda; Meiva Marthaulina Lestari Siahaan (Fakultas Tarbiyah Universitas Ibrahimy, 2022)
The purpose of the study was to determine the ability of students in solving the national assessment problem model. The study belonged to qualitative approach. The research was conducted at SMPK Putra St. Xavier Kefamenanu. The data conducted from test results of national assessment collection problems and selected-participants interviews. The collected data then identified based on the following stages: data reduction, data presentation, conclusion and verification. The results of data analysis showed that the level of students' ability in completing the national assessment model problems in the percentage is the low-level ability category of 30%, at the medium level by 60% and the high level by 10%. The findings of this study: students with high math ability master all components of MCA in terms of content, cognitive processes, and context; students with moderate math abilities are able to master reading literacy content but are weak in numeracy literacy; students with low math abilities are very weak in content, cognitive processes, and context. In terms of cognitive processes, students with moderate mathematical ability can find and interpret text content but fail to integrate and evaluate text content into mathematical concepts and procedures and the context of the questions that can be worked on are personal and scientific. In cognitive process, students with low mathematical abilities can find information but are unable to interpret it to evaluate the content of the text into a mathematical concept and procedure.